A solar cell and its preparation method, photovoltaic module
By using hole modification layers containing compounds of formula (I) and self-assembled single-molecule materials in perovskite solar cells, the defect problem caused by imperfect accumulation of the hole transport layer is solved, and the photoelectric conversion performance of solar cells is improved and stability, suitable for large size and suede structure perovskite solar cells.
Patent Information
- Application Number
- CN202411414828.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-11
AI Technical Summary
In existing perovskite solar cells, hole modification layer defects are caused by imperfect accumulation of self-assembled single-molecule materials on the surface of the hole transport layer, which affects the photoelectric conversion performance and stability of the solar cell.
Using hole-modified layers containing compounds of formula (I) and self-assembled single-molecule materials, the film-forming uniformity and interface modification ability of hole-modified layers are improved by regulating the mass ratio of the compound and spin coating conditions, reducing defects and enhancing bluntness. ability to transform.
It significantly improves the photoelectric conversion efficiency and stability of solar cells and reduces leakage current. It is suitable for large-size solar cells and perovskite solar cells with suede structure.
Smart Images

Figure CN118922003B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of solar cells, and in particular to a solar cell and a preparation method thereof, and a photovoltaic module. Background Art
[0002] Perovskite solar cell is a device that converts solar energy into electrical energy. It has good photoelectric properties, simple device structure and low manufacturing cost.
[0003] In perovskite solar cells, the hole transport layer plays an important role in the photoelectric conversion performance of the solar cell. The hole modification layer is a thin film containing self-assembled monomolecular materials, which can improve the performance of the hole transport layer. However, at present, due to the inevitable imperfect accumulation of self-assembled monomolecular materials on the surface of the hole transport layer, the hole modification layer will inevitably produce defects. Summary of the invention
[0004] In order to solve the above technical problems, the present application discloses a solar cell and a preparation method thereof, and a photovoltaic module to improve the film formation uniformity of the hole modification layer, reduce the defects of the hole modification layer, and thus improve the performance of the solar cell.
[0005] In a first aspect, the present application provides a solar cell, comprising a substrate and a hole transport layer, a hole modification layer and a perovskite layer sequentially arranged on the substrate, wherein the hole modification layer is located between the hole transport layer and the perovskite layer; the hole modification layer comprises a compound represented by formula (I) and a self-assembled monomolecular material, and the self-assembled monomolecular material comprises at least one of a compound represented by formula (II) and a compound represented by formula (III),
[0006] , , ,
[0007] Among them, 2≤n≤5, 2≤x≤4, 2≤y≤4.
[0008] In some embodiments of the present application, the mass percentage of the compound represented by formula (I) in the hole modification layer is a, 30%≤a≤70%, and the mass percentage of the compound represented by formula (II) in the hole modification layer is b, 30%≤b≤70%.
[0009] In some embodiments of the present application, 0.4≤a / b≤2.5.
[0010] In some embodiments of the present application, 0.6≤a / b≤0.9.
[0011] In some embodiments of the present application, the contact angle of the self-assembled monomolecular material is 33°~55°.
[0012] In some embodiments of the present application, the surface root mean square (RMS) roughness of the hole modification layer is no greater than 1 nm.
[0013] In some embodiments of the present application, the self-assembled monomolecular material is selected from at least one of the following compounds:
[0014] , , ,
[0015] , , .
[0016] In some embodiments of the present application, the size of the solar cell is not less than 50 mm×50 mm.
[0017] In some embodiments of the present application, the solar cell includes a perovskite tandem solar cell, the substrate includes a bottom cell and a composite layer stacked on the bottom cell, the hole transport layer, the hole modification layer and the perovskite layer are stacked on the composite layer in sequence, and the surface of the composite layer facing the hole transport layer has a suede structure.
[0018] In some embodiments of the present application, an electron transport layer, a buffer layer, a first transparent electrode layer and an anti-reflection layer are sequentially stacked on the perovskite layer.
[0019] In a second aspect, the present application provides a method for preparing a solar cell as described in the first aspect, comprising the following steps:
[0020] Providing the substrate, and preparing a hole transport layer on the surface of the composite layer of the substrate, wherein the hole transport layer includes nickel oxide;
[0021] Applying a first solution on the surface of the hole transport layer to form the hole modification layer, wherein the first solution contains a compound represented by formula (I) and a self-assembled monomolecular material, wherein the self-assembled monomolecular material includes at least one of a compound represented by formula (II) and a compound represented by formula (III);
[0022] Other functional layers are sequentially prepared on the surface of the hole modification layer, and the other functional layers at least include a perovskite layer, an electron transport layer and a first transparent electrode layer.
[0023] In some embodiments of the present application, in the first solution, the mass ratio of the compound represented by formula (I) to the self-assembled monomolecular material is 0.4-2.5:1.
[0024] In some embodiments of the present application, in the first solution, the mass ratio of the compound represented by formula (I) to the self-assembled monomolecular material is 0.6-0.9:1.
[0025] In some embodiments of the present application, the preparation process of the hole modification layer includes:
[0026] The first solution is spin-coated on the surface of the hole transport layer, and the hole modification layer is obtained after annealing, wherein the spin-coating speed is 3000rpm~5000rpm, the spin-coating time is 20s~40s, the annealing temperature is 80℃~120℃, and the annealing time is 8min~12min.
[0027] In some embodiments of the present application, the preparation method further comprises:
[0028] A perovskite layer, an electron transport layer, a buffer layer, a first transparent electrode layer and an anti-reflection layer are prepared on the surface of the hole modification layer.
[0029] In a third aspect, the present application provides a photovoltaic module, wherein the photovoltaic module includes the solar cell as described in the first aspect, or the photovoltaic module includes the solar cell prepared by the preparation method as described in the second aspect.
[0030] Compared with the prior art, this application has at least the following beneficial effects:
[0031] The present application provides a solar cell and a preparation method thereof, and a photovoltaic module, wherein the hole modification layer of the solar cell comprises a compound represented by formula (I) and a self-assembled monomolecular material, and the self-assembled monomolecular material comprises at least one of a compound represented by formula (II) and a compound represented by formula (III). Under the joint action of the compound represented by formula (I) and the self-assembled monomolecular material, the interface modification ability and passivation ability of the hole modification layer on the hole transport layer can be greatly improved, thereby improving the photoelectric conversion efficiency and other performance of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 This is a schematic diagram of the structure of a solar cell in one embodiment of the present application;
[0034] Figure 2 This is a schematic diagram of the structure of a solar cell in another embodiment of the present application;
[0035] Figure 3 The photoluminescence spectrum (PL) diagram is a graph of the compound represented by formula (I), the compound represented by formula (II-3), and a mixture of the two compounds at a mass ratio of 1:1;
[0036] Figure 4 The time-resolved fluorescence spectra (TRPL) of the compound represented by formula (I), the compound represented by formula (II-3), and a mixture of the two compounds at a mass ratio of 1:1;
[0037] Figure 5 Nickel oxide (NiO x ) material, the compound represented by formula (I), the compound represented by formula (II-3), and the contact angle test graph after the two compounds are mixed in a mass ratio of 1:1;
[0038] Figure 6 Atomic force microscope (AFM) images of the surface of the SAM layer formed by mixing the compound represented by formula (II-3) and the compound (I) and the compound (II-3) in a mass ratio of 1:1;
[0039] Figure 7 The infrared AFM images of the surface of the SAM layer formed by mixing the compound represented by formula (II-3) and the compound (I) and the compound (II-3) in a mass ratio of 1:1 are shown.
[0040] Explanation of the accompanying drawings: 1-substrate, 2-hole transport layer, 3-hole modification layer, 4-perovskite layer, 5-electron transport layer, 6-buffer layer, 7-first transparent electrode layer, 8-anti-reflection layer, 10-bottom cell, 11-second transparent electrode layer, 12-P-type doped crystalline silicon layer, 13-first intrinsic amorphous silicon layer, 14-N-type silicon wafer, 15-second intrinsic amorphous silicon layer, 16-N-type doped crystalline silicon layer, 17-composite layer, 21-positive electrode, 22-back electrode. DETAILED DESCRIPTION
[0041] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0042] In the present application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings. These terms are mainly used to better describe the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation.
[0043] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.
[0044] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0045] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.
[0046] The technical solution of the present application will be further described below in conjunction with embodiments and drawings.
[0047] At present, due to the self-assembled monolayer materials based on nickel oxide (NiO x ) will inevitably produce defects on the hole modification layer due to the inevitable imperfect accumulation on the hole transport layer surface. These defects will expose the nickel oxide surface in the underlying hole transport layer, resulting in leakage current at the interface of these defective locations, affecting the performance and stability of solar cells. Therefore, how to improve the film formation uniformity of the hole modification layer to reduce its defects has become a technical problem that needs to be solved urgently.
[0048] In view of this, in a first aspect, the present application provides a solar cell, such as Figure 1As shown, the solar cell includes a substrate 1 and a hole transport layer 2, a hole modification layer 3 and a perovskite layer 4 sequentially arranged on the substrate 1. The hole modification layer 3 is located between the hole transport layer 2 and the perovskite layer 4. The hole modification layer 3 includes a compound represented by formula (I) and a self-assembled monomolecular material, and the self-assembled monomolecular material includes at least one of a compound represented by formula (II) and a compound represented by formula (III).
[0049] , , ,
[0050] Among them, 2≤n≤5, 2≤x≤4, 2≤y≤4.
[0051] The inventors of the present application unexpectedly discovered that by combining the compound represented by formula (I) (hereinafter referred to as compound (I)) with at least one of the compound represented by formula (II) (hereinafter referred to as compound (II)) and the compound represented by formula (III) (hereinafter referred to as compound (III)), that is, the hole modification layer contains both the above compound (I) and the above self-assembled monomolecular material. Compared with the hole modification layer containing only the above self-assembled monomolecular material, the hole modification layer of the present application has greatly improved the interface modification ability and passivation ability of the hole transport layer, so that the photoelectric conversion performance and stability of the solar cell are greatly improved. This may be because, on the one hand, the compound (I) and the above self-assembled monomolecular material interact with each other, and the compound (I) can fill the position that the above self-assembled monomolecular material cannot fill, thereby improving the coverage of the self-assembled monomolecular material on the surface of the nickel oxide hole transport layer, thereby greatly improving the film formation uniformity of the hole modification layer and reducing the defects in the hole modification layer. The reduction of defects can further reduce the nickel oxide (NiO x) surface exposure, thereby reducing the leakage current generated at the interface; on the other hand, the above self-assembled monomolecular material will spontaneously form clusters in the solution used to prepare the hole modification layer. By introducing compound (I) to disperse the formed clusters, the uniformity and coverage of the hole modification layer film layer are improved, so that it is more firmly anchored on the surface of the hole transport layer, and the defects on the surface of the hole transport layer are more fully passivated. Taking compound (II) and compound (II-3) (i.e. 7H-DC) as an example, theoretical calculations show that the average binding energy of compound (II-3) to form a dimer is -0.418 eV / mole, the average binding energy to form a trimer is -0.609 eV / mole, and the average binding energy to form a tetramer is -0.680 eV / mole, which shows that compound (II-3) is easy to spontaneously form high-order clusters. After the introduction of compound (I), compound (I) can make compound (II-3) more evenly distributed in the hole modification layer. The dimer binding energy of compound (I) and compound (II-3) is -0.442 eV / mole, the dimer binding energy of compound (II-3) is -0.418 eV / mole, and the dimer binding energy of compound (I) is -0.388 eV / mole. It can be seen that the binding energy between compound (II-3) and compound (I) is greater than the binding energy of each of them forming a dimer alone. Similarly, the binding energy analysis of the trimer also has similar results, indicating that compound (II-3) prefers to bind to compound (I), thereby limiting compound (II-3) from binding alone to form large clusters.
[0052] In addition, the ammonium end group of compound (I) can also coordinate with perovskite through ionic interaction to passivate the perovskite layer interface at the bottom of the hole modification layer.
[0053] In addition, compound (II) can also regulate NiO x The band structure of the perovskite increases the open circuit voltage, and compound (II) also has the function of loosening the bottom of the skeleton layer of the perovskite, which is conducive to a more complete reaction between lead iodide and the cationic solution. Under the combined effect of the above factors, the solar cell has better photoelectric conversion performance and stability.
[0054] The number of carbon atoms in the compound (I) of the present application is 2 to 5. For example, when the number of carbon atoms is 5, the compound (I) may be:
[0055] ,
[0056] The compound is 6-(iodo-λ5-aza-yl)hexanoic acid, abbreviated as IAHA.
[0057] In an optional embodiment, the mass percentage of compound (I) in the hole modification layer is a, 30%≤a≤70%, and the mass percentage of compound (II) in the hole modification layer is b, 30%≤b≤70%. By adjusting the contents of compound (I) and compound (II) within the above range, it is more conducive to obtaining a hole modification layer with excellent interface modification ability and passivation ability.
[0058] In an optional embodiment, 0.4≤a / b≤2.5; in another optional embodiment, 0.6≤a / b≤0.9. The inventors have found that when a / b is too small (for example, a / b is less than 0.4), it indicates that the relative content of compound (I) is low, which is not conducive to the film formation uniformity of the hole modification layer; when a / b is too large (for example, a / b is greater than 2.5), it indicates that the relative content of the above self-assembled monomolecular material is low, which is not conducive to the hole modification layer to fully passivate the surface defects of the hole transport layer. By regulating a / b within the above range, the film formation uniformity of the hole modification layer can be greatly improved while effectively passivating the defects on the surface of the hole transport layer, which is conducive to improving the interface modification ability and passivation ability of the hole modification layer to the hole transport layer.
[0059] In an optional embodiment, the contact angle of the self-assembled monomolecular material is 33°~55°, indicating that the self-assembled monomolecular material of the present application has excellent wettability, which is beneficial to improving the uniformity of film formation of the hole modification layer, thereby reducing the number of defects in the hole modification layer, and is beneficial to improving the interface modification ability and passivation ability of the hole modification layer to the hole transport layer.
[0060] In an optional embodiment, the surface RMS roughness of the hole modification layer is no more than 1 nm, and has good film-forming uniformity.
[0061] In an optional embodiment, the self-assembled monomolecular material is selected from at least one of the following compounds:
[0062] , , ,
[0063] , , .
[0064] The above compounds (II-1) to (III-3) have the same or similar functional groups and thus have similar chemical properties. When used in combination with compound (I), it is beneficial to improve the interface modification and passivation ability of the hole modification layer to the hole transport layer. In addition, since compound (II-1) and compound (II-2) have the same functional groups as compound (II-3), the only difference between them is the length of the carbon chain. Therefore, the binding energy analysis results of compound (II-1) and compound (II-2) are similar to those of compound (II-3), and will not be repeated in this application.
[0065] The present application has no particular limitation on the thickness of the hole modification layer, as long as the purpose of the present invention can be achieved. For example, the thickness of the hole modification layer is 0.5 nm to 5 nm, which is conducive to obtaining a hole modification layer with excellent interface modification ability and passivation ability.
[0066] In an optional embodiment, the size of the solar cell is not less than 50mm×50mm. For example, the size of the solar cell may be 50mm×50mm, 182mm×182mm or 210mm×210mm. It is understandable that as the size of the solar cell increases, the area of the hole modification layer increases, resulting in an increased possibility of defects in the hole modification layer. Since the hole modification layer of the present application includes compound (I) and the above-mentioned self-assembled monomolecular material, it can effectively passivate the defects on the surface of the hole transport layer while greatly improving the film formation uniformity of the hole modification layer, thereby reducing the defects in the hole modification layer, and is therefore more suitable for large-sized solar cells.
[0067] In an optional embodiment, reference Figure 1 , the solar cell includes a perovskite tandem solar cell. The substrate 1 includes a bottom cell 10 and a composite layer 17 stacked on the bottom cell 10, wherein a hole transport layer 2, a hole modification layer 3 and a perovskite layer 4 are sequentially stacked on the composite layer 17, and the composite layer 17 has a velvet structure on the side facing the hole transport layer 2. The bottom cell 10 includes a second transparent electrode layer 11, a P-type doped crystalline silicon layer 12, a first intrinsic amorphous silicon layer 13, an N-type silicon wafer 14, a second intrinsic amorphous silicon layer 15 and an N-type doped crystalline silicon layer 16 from bottom to top. In addition, an electron transport layer 5 and a first transparent electrode layer 7 are sequentially stacked on the perovskite layer 4.
[0068] The substrate of the present application can be a solar cell with a crystalline silicon bottom cell as the substrate, and the present application does not impose any restrictions on this. In order to better absorb solar energy, the composite layer of the present application has a velvet structure on the surface of the side facing the hole transport layer (that is, the light incident surface). For example, the velvet structure can adopt a pyramid-shaped velvet structure. Through the velvet structure, it is possible to provide a higher surface area for the solar cell while reducing the reflection and diffusion of light. The surface of the hole transport layer is consistent with the velvet structure shape of the composite layer, both of which are pyramid-shaped, thereby achieving the shape preservation requirements of the velvet structure. The present application has no special restrictions on the preparation method of the velvet structure, as long as the purpose of the present application can be achieved. For example, it can be prepared by the existing magnetron sputtering method.
[0069] The inventors found that since the velvet structure is a "pyramid" structure, it becomes more difficult to prepare a hole modification layer with uniform thickness and few defects when preparing a hole transport layer and a hole modification layer on the surface of such a composite layer. Since the self-assembled monomolecular material of the hole modification layer of the present application includes compound (I) and compound (II), it can effectively passivate the defects on the surface of the hole transport layer while greatly improving the film formation uniformity of the hole modification layer, thereby reducing the defects in the hole modification layer, and is more suitable for solar cells with a velvet structure.
[0070] In an optional embodiment, if Figure 2 As shown, an electron transport layer 5, a buffer layer 6, a first transparent electrode layer 7 and an anti-reflection layer 8 are sequentially stacked on the perovskite layer 4. The buffer layer 6 is located on the surface of the electron transport layer 5 facing away from the perovskite layer 4 (i.e., the light incident surface), and the anti-reflection layer 8 is located on the surface of the first transparent electrode layer 7 facing away from the buffer layer 6. The solar cell containing the anti-reflection layer has a higher photoelectric conversion efficiency.
[0071] The present application has no particular restrictions on the electrodes of the solar cell, as long as the purpose of the present application can be achieved. Figure 1 and Figure 2 A positive electrode 21 may be provided on the light-receiving surface of the solar cell, and a back electrode 22 may be provided on the backlight surface of the solar cell.
[0072] The hole modification layer, hole transport layer, perovskite layer and electron transport layer of the present application can also be applied to single-junction perovskite solar cells. The present application has no particular restrictions on the structure of single-junction perovskite solar cells, which can be existing single-junction perovskite solar cell structures.
[0073] In a second aspect, the present application provides a method for preparing a solar cell as described in the first aspect, comprising the following steps:
[0074] Preparation of a hole transport layer: providing a substrate, and preparing a hole transport layer on the surface of the composite layer of the substrate, wherein the hole transport layer includes nickel oxide;
[0075] Preparation of the hole modification layer: coating a first solution on the surface of the hole transport layer to form the hole modification layer, wherein the first solution contains compound (I) and a self-assembled monomolecular material, and the self-assembled monomolecular material includes at least one of compound (II) and compound (III);
[0076] Preparation of other functional layers: other functional layers are sequentially prepared on the surface of the hole modification layer, and the other functional layers at least include a perovskite layer, an electron transport layer and a first transparent electrode layer.
[0077] In the preparation step of the hole transport layer, the hole transport layer material can be deposited on the composite layer surface of the substrate by magnetron sputtering to form a hole transport layer with a thickness of 10nm to 25nm. The hole transport layer material includes nickel oxide (NiO x ).
[0078] In the preparation step of the hole modification layer, the compound (I) can be first prepared into solution A, the self-assembled monomolecular material can be prepared into solution B, and then solution A and solution B can be mixed in a desired ratio to obtain a first solution; or, the compound (I) and the self-assembled monomolecular material can be directly added to the solvent in a corresponding mass ratio, and the first solution can be obtained after dissolution. The present application has no particular restriction on the order of adding the compound (I) and the self-assembled monomolecular material, as long as the first solution can be obtained.
[0079] The present application has no particular restrictions on the solvents in solution A, solution B and the first solution, for example, they may include but are not limited to ethanol, isopropanol, etc. In addition, the present application may adopt spin coating, blade coating, spray coating, slit coating, etc. to prepare the hole modification layer, and the present application has no particular restrictions.
[0080] In the preparation of other functional layers, the prepared other functional layers may further include a buffer layer and an anti-reflection layer.
[0081] In an optional embodiment, in the first solution, the mass ratio of compound (I) to the self-assembled monomolecular material is 0.4-2.5: 1, preferably 0.6-0.9: 1. By regulating the mass ratio of compound (I) to the self-assembled monomolecular material within the above range, the film formation uniformity of the hole modification layer can be greatly improved under the joint action of the above two compounds, while effectively passivating the defects on the surface of the hole transport layer.
[0082] In an optional embodiment, the preparation process of the hole modification layer includes:
[0083] The first solution is spin-coated on the surface of the hole transport layer, and the hole modification layer is obtained after annealing, wherein the spin-coating speed is 3000 rpm to 5000 rpm, the spin-coating time is 20 s to 40 s, the annealing temperature is 80° C. to 120° C., and the annealing time is 8 min to 12 min. By regulating the spin-coating speed, the spin-coating time, the annealing temperature and the annealing time within the above range, it is beneficial to obtain a hole modification layer with good film uniformity and a small number of defects.
[0084] In an optional embodiment, the preparation method further comprises:
[0085] A perovskite layer, an electron transport layer, a buffer layer, a first transparent electrode layer and an anti-reflection layer are prepared on the surface of the hole modification layer.
[0086] When preparing the perovskite layer, a skeleton layer can be prepared first, and then an organic salt solution can be spin-coated onto the surface of the skeleton layer, and the perovskite layer can be obtained after thermal annealing. The skeleton layer can be obtained by evaporating PbI2 and CsX (X represents a halogen element). The present application has no particular restrictions on the type of organic salt. For example, at least two of formamidine hydroiodide (FAI), formamidine hydrobromide (FABr), formamidine hydrochloride (FACl), methylammonium iodide (MAI), methylammonium bromide (MABr) and methylammonium chloride (MACl) can be combined and dissolved in a solvent to obtain an organic salt solution. The present application has no particular restrictions on the coating method. For example, spin coating, spray coating, slit coating, blade coating and the like can be used. The thickness of the perovskite layer is 400nm~500nm.
[0087] The present application has no particular restrictions on the preparation methods of the electron transport layer, the buffer layer, the first transparent electrode layer, the anti-reflection layer and the electrode. 60 The electron transport layer can be obtained by thermal evaporation deposition using a metal evaporation device, and the thickness is 10 nm~20 nm; the buffer layer material SnO2 can be obtained by atomic layer deposition (ALD) method to obtain a buffer layer with a thickness of 10 nm~17 nm; the transparent electrode layer material indium gallium zinc oxide (IZO) can be obtained by magnetron sputtering method to obtain a first transparent electrode layer with a thickness of 70 nm~110 nm; the anti-reflection layer material LiF or MgF2 can be obtained by thermal evaporation deposition using a metal evaporation device to obtain an anti-reflection layer with a thickness of 80 nm~130 nm; the electrode material Ag can be obtained by thermal evaporation deposition using a metal evaporation device to obtain a positive electrode and a back electrode, and the electrode thickness is 300 nm~500 nm.
[0088] The present application has no particular limitation on the synthesis method of compound (I), compound (II) and compound (III), and they can be synthesized by existing synthesis methods.
[0089] Illustratively, compound (I) can be synthesized by the following steps:
[0090] Add aminocaproic acid (1 g, 7.6 mmol) into a flask (100 mL) and dissolve in ethanol (20 mL) under argon protection. Add 1 mL, 8.4 mmol of hydrated acid (58 wt% in H2O) dropwise into the solution at 0°C, slowly warm to room temperature, and stir for 1 h. After removing the solvent, the crude product was washed with ether to obtain 1.8 g of a white solid with a yield of 90%, which is compound (I): 6-(iodo-λ5-aza-yl)hexanoic acid.
[0091] For example, compound (II-3) can be synthesized by the following steps:
[0092] Step 1.1, 7H-dibenzocarbazole (DCB) (1.20 g, 4.49 mmol) was dissolved in 1,4-dibromobutane (10.7 mL, 89.78 mmol), tetrabutylammonium bromide (TBAB) (0.29 g, 0.90 mmol) and 50% KOH aqueous solution (2.5 ml, 22.44 mmol). The reaction mixture was heated to 60 ° C and stirred overnight. After the reaction was completed, the reaction mixture was extracted with dichloromethane. The organic layer was dried over anhydrous MgSO4, and the solvent was distilled under reduced pressure. The crude product was purified by silica gel column chromatography with petroleum ether / dichloromethane (v / v, 4 / 1) as the eluent to obtain a white solid 7-(4-bromobutyl)-7h-dibenzo[c,g]carbazole, i.e. 4BrDCB (1.40 g, yield 77%);
[0093] Step 1.2: The product obtained in step 1.1 (1.00 g, 2.49 mmol) was dissolved in triethyl phosphite (8.6 mL, 49.71 mmol), heated under reflux for 16 h, cooled to room temperature, poured into 200 mL of petroleum ether, and stirred at -70 ° C until no solid precipitated. Subsequently, the solid was filtered out and washed with petroleum ether to obtain a white solid 4-(7h-dibenzo[c,g]carbazole-7-yl)butylphosphonic acid diethyl ester, i.e. 4PDCB (0.85 g, 74%).
[0094] Step 1.3: The product obtained in step 1.2 (0.65 g, 1.41 mmol) was dissolved in anhydrous 1,4-dioxane (15 mL) under an argon atmosphere, and bromotrimethylsilane (1.9 mL, 14.14 mmol) was added dropwise. The reaction mixture was stirred at room temperature for 24 h under an argon atmosphere, and then methanol (3 mL) was added and stirred for 3 h. Finally, distilled water (20 mL) was added dropwise until the solution became opaque. The product was filtered out and the filtered product was washed with water to obtain a light green compound (II-3): (4-(7h-dibenzo[c,g]carbazole-7-yl)butyl)phosphonic acid, i.e. 7H-DC.
[0095] The synthesis process of compound (II-1), compound (II-2), compound (III-1) to compound (III-3) is similar to the synthesis process of compound (II-3), and will not be repeated in this application.
[0096] The preparation method of the solar cell provided in the present application can prepare a hole modification layer with good film uniformity and a small number of defects, so that the hole modification layer has a greatly improved interface modification ability and passivation ability for the hole transport layer, thereby improving the photoelectric conversion efficiency and other performances of the perovskite solar cell. In addition, the preparation method of the present application has the advantages of simple preparation process and convenient operation, which is conducive to industrial production and suitable for large-scale manufacturing of perovskite silicon tandem solar cells.
[0097] In a third aspect, the present application provides a photovoltaic module, wherein the photovoltaic module includes the solar cell as described in the first aspect, or the photovoltaic module includes the solar cell prepared by the preparation method as described in the second aspect.
[0098] The present application also provides a photovoltaic module, which is used to convert received light energy into electrical energy and transmit it to an external load. The photovoltaic module includes: at least one battery string, which is formed by connecting a plurality of the above-mentioned solar cells; a packaging film, which is used to cover the surface of the battery string; and a cover plate, which is used to cover the surface of the packaging film away from the battery string.
[0099] The solar cell and its preparation method, and the photovoltaic module of the embodiment of the present application are further described below in conjunction with more specific embodiments.
[0100] Example 1
[0101] <Preparation of composite layer>
[0102] A bottom cell with a size of 50 mm×50 mm is provided, and a 20 nm thick indium tin oxide (ITO) film is prepared as a composite layer on the light-receiving surface of the bottom cell. In the bottom cell, the thickness of the N-type doped crystalline silicon layer is 6 nm, the thickness of the first intrinsic amorphous silicon layer is 8 nm, the thickness of the N-type silicon wafer is 120 μm, the thickness of the second intrinsic amorphous silicon layer is 8 nm, the thickness of the P-type doped crystalline silicon layer is 10 nm, and the thickness of the second transparent electrode layer is 100 nm.
[0103] <Preparation of hole transport layer>
[0104] A nickel oxide hole transport layer with a thickness of 20 nm is deposited on the surface of the composite layer of the substrate by magnetron sputtering.
[0105] <Preparation of Hole Modification Layer>
[0106] Compound (I) IAHA was dissolved in ethanol to obtain a solution A with a concentration of 1 mg / mL, and compound (II-3) was dissolved in ethanol to obtain a solution B with a concentration of 1 mg / mL, and then solution A and solution B were mixed in a volume ratio of 3:7 to obtain a first solution. Then, a hole modification layer wet film was formed by spin coating the first solution, wherein the bottom battery with a hole transport layer was first adsorbed on a spin coater, and then 100 μL of the first solution was sucked with a pipette and titrated on the surface of the hole transport layer, the spin coating speed was 4000 rpm, the spin coating time was 30 s, and after annealing, a hole modification layer with a thickness of 5 nm was obtained, the annealing temperature was 100°C, and the annealing time was 10 min.
[0107] <Preparation of Perovskite Layer>
[0108] PbI2 and CsBr were co-evaporated at a rate of 10:1 and thermally evaporated to obtain a skeleton layer; the organic salts FAI, MABr, and MACl were mixed in a mass ratio of 80.9:13.2:5.9 and then added to ethanol to obtain an organic salt cation solution with a concentration of 0.65 mmol / mL; the organic salt cation solution was then spin-coated onto the surface of the skeleton layer, and after the organic salt cations fully reacted with the skeleton layer, a perovskite layer with a thickness of 450 nm was obtained.
[0109] <Preparation of other functional layers>
[0110] An electron transport layer, a buffer layer and a first transparent electrode layer are sequentially prepared on the surface of the perovskite layer.
[0111] The preparation process of the electron transport layer is as follows: a 20 nm thick C layer is evaporated on the perovskite layer. 60as an electron transport layer; the preparation process of the buffer layer is as follows: a 10 nm thick tin dioxide layer is prepared on the electron transport layer by atomic layer deposition as a buffer layer; the preparation process of the first transparent electrode layer is as follows: a 100 nm thick IZO layer is prepared on the electron transport layer by magnetron sputtering as the first transparent electrode layer.
[0112] <Preparation of Solar Cells>
[0113] A 350 nm thick silver layer is prepared on the first transparent electrode layer by thermal evaporation as the positive electrode, and a 300 nm thick silver layer is prepared on the second transparent electrode layer of the bottom cell by thermal evaporation as the back electrode. Then, MgF2 is deposited by thermal evaporation through a metal evaporation device to obtain an anti-reflection layer with a thickness of 100 nm, and a solar cell is obtained. The cell structure is as follows: Figure 2 shown.
[0114] Embodiment 2 to Embodiment 7
[0115] The process was the same as Example 1 except that in <Preparation of Hole Modification Layer>, the volume ratio of solution A to solution B was adjusted according to Table 1 to adjust the contents of compound (I) and compound (II-3) in the hole modification layer.
[0116] Embodiment 8~embodiment 11
[0117] Except that the spin coating speed, spin coating time, annealing temperature and annealing time are adjusted according to Table 1 in <Preparation of Hole Modification Layer>, the rest is the same as Example 1.
[0118] Example 12
[0119] Except that the size of the bottom cell is adjusted to 182 mm×182 mm in <Preparation of composite layer>, the rest is the same as Example 1.
[0120] Comparative Example 1
[0121] Except for the difference in <Preparation of Hole Modification Layer> from Example 1, the rest is the same as Example 1.
[0122] <Preparation of Hole Modification Layer>
[0123] Compound (II-3) was dissolved in ethanol to obtain a solution B with a concentration of 1 mg / mL. Then, the solution B was spin-coated to form a wet film of the hole modification layer. The bottom battery with the hole transport layer was first adsorbed on the spin coater, and then 500 μL of solution B was aspirated with a pipette and titrated on the surface of the hole transport layer. The spin coating speed was 4000 rpm and the spin coating time was 30 s. After annealing, a hole modification layer with a thickness of 5 nm was obtained. The annealing temperature was 100°C and the annealing time was 10 min.
[0124] Table 1 Preparation parameters of Example 1 to Example 11 and Comparative Example 1
[0125]
[0126] In Table 1, “ / ” indicates that there is no relevant preparation parameter.
[0127] Performance Testing
[0128] Solar cell performance test:
[0129] The current (I)-voltage (V) of the solar cells of each embodiment and comparative example was measured using an IV tester (model: MX-MPVC-A20, manufacturer: Suzhou Maxwell Technology Co., Ltd.) to obtain the short-circuit current (Jsc), fill factor (FF), open-circuit voltage (Voc) and photoelectric conversion efficiency (Eta) of the solar cells.
[0130] Table 2 Performance data of various embodiments and comparative examples
[0131]
[0132] It can be seen from Examples 1 to 12 and Comparative Example 1 that the short-circuit current of the solar cell of the present application is significantly improved compared to Comparative Example 1, and the photoelectric conversion efficiency is improved.
[0133] In order to verify the effect of the combination of compound (I) and compound (II) of the present application, compound (I), compound (II-3), and a mixture of the two in a mass ratio of 1:1 were respectively prepared into a first solution with a concentration of 1 mg / mL, and then SAM layers were prepared on the surface of a perovskite film with a thickness of 450 nm, and photoluminescence spectroscopy (PL) tests and time-resolved fluorescence spectroscopy (TRPL) tests were performed.
[0134] Figure 3 The PL images of compound (I), compound (II-3) and a mixture of the two compounds at a mass ratio of 1:1 are shown in Figure 2. Figure 3 It can be seen that after the mixture of compound (I) and compound (II-3), the ability to extract holes becomes stronger than that of single compound (I) and compound (II-3), indicating that there is effective hole transfer under the joint action of the two, which is beneficial to the improvement of the interface modification ability of the hole transport layer.
[0135] Figure 4 The TRPL graphs of compound (I), compound (II-3) and a mixture of the two compounds at a mass ratio of 1:1 are shown in FIG. Figure 4It can be seen that after the compound (I) and the compound (II-3) are mixed, the perovskite film has a longer luminescence lifetime, indicating that under the joint action of the two, there are fewer defects at the interface and non-radiative recombination is suppressed, which is beneficial to the improvement of the passivation ability of the hole transport layer.
[0136] Figure 5 (a) is nickel oxide (NiO x ) The contact angle of the material, Figure 5 (b) is the contact angle of compound (I), Figure 5 (c) is the contact angle of compound (II-3), Figure 5 (d) is the contact angle measured after compound (I) and compound (II-3) were mixed in a mass ratio of 1:1. Figure 5 It can be seen that NiO x The contact angle of the material is small, about 2°, while the contact angles of compound (I) and compound (II-3) are relatively large (33.2° and 48.4°, respectively). However, when the two are mixed according to the mass ratio, the contact angle of the resulting mixture increases significantly (reaching 54.8°). It can be seen that compound (I) and compound (II-3) have a synergistic effect in increasing the contact angle.
[0137] In order to verify the effect of the combination of compound (I) and compound (II) of the present application, compound (II-3) and a mixture of compound (I) and compound (II-3) in a mass ratio of 1:1 were respectively prepared into solutions with a concentration of 1 mg / mL, and then SAM layers were prepared on the surface of ITO glass, and the SAM layers were observed by AFM.
[0138] Figure 6 (a) is an AFM image of the surface of the SAM layer formed by compound (II-3); Figure 6 (b) is an AFM image of the surface of the SAM layer formed by mixing compound (I) and compound (II-3). It can be seen that the RMS roughness of the SAM layer formed by compound (II-3) alone is relatively high, with an RMS value of 2.11 nm, while the RMS roughness of the SAM layer formed by mixing compound (I) and compound (II-3) is lower, with an RMS value of 0.97 nm.
[0139] Figure 7 (a) is an infrared AFM image of the surface of the SAM layer formed by compound (II-3); Figure 7(b) is an infrared AFM image of the surface of the SAM layer formed by mixing compound (I) and compound (II-3). It can be seen that in the SAM layer formed by compound (II-3) alone, the distribution of bright and dark areas is uneven, indicating that its uniformity is low; while in the SAM layer formed by mixing compound (I) and compound (II-3), the distribution of bright and dark areas is relatively uniform, indicating that its uniformity is higher.
[0140] The above is a detailed introduction to a solar cell and its preparation method, and a photovoltaic module disclosed in the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions and core inventions of the embodiments of the present application. At the same time, for general technicians in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A solar cell, characterized in that: It comprises a substrate and a hole transport layer, a hole modification layer and a perovskite layer sequentially arranged on the substrate, wherein the hole modification layer is located between the hole transport layer and the perovskite layer; The hole modification layer comprises a compound represented by formula (I) and a self-assembled monomolecular material, wherein the self-assembled monomolecular material comprises at least one of a compound represented by formula (II) and a compound represented by formula (III), 、 、 , Among them, 2≤n≤5, 2≤x≤4, 2≤y≤4.
2. The solar cell according to claim 1, characterized in that: The mass percentage of the compound represented by formula (I) in the hole modification layer is a, 30%≤a≤70%, and the mass percentage of the compound represented by formula (II) in the hole modification layer is b, 30%≤b≤70%.
3. The solar cell according to claim 2, characterized in that: 0.4≤a / b≤2.
5.
4. The solar cell according to claim 2, characterized in that: 0.6≤a / b≤0.
9.
5. The solar cell according to any one of claims 1 to 4, characterized in that: The contact angle of the self-assembled monomolecular material is 33° to 55°.
6. The solar cell according to claim 1, characterized in that: The surface RMS roughness of the hole modification layer is no greater than 1 nm.
7. The solar cell according to claim 1, characterized in that: The self-assembled monomolecular material is selected from at least one of the following compounds: 、 、 、 、 、 。 8. The solar cell according to any one of claims 1 to 4, characterized in that: The size of the solar cell is not less than 50 mm×50 mm.
9. The solar cell according to claim 8, characterized in that: The solar cell comprises a perovskite stacked solar cell, the substrate comprises a bottom cell and a composite layer stacked on the bottom cell, the hole transport layer, the hole modification layer and the perovskite layer are stacked on the composite layer in sequence, and the surface of the composite layer facing the hole transport layer has a velvet structure.
10. The solar cell according to claim 9, characterized in that: An electron transport layer, a buffer layer, a first transparent electrode layer and an anti-reflection layer are sequentially stacked on the perovskite layer.
11. A method for preparing a solar cell according to any one of claims 1 to 10, characterized in that: The following steps are involved: Providing a substrate, and preparing a hole transport layer on the surface of the composite layer of the substrate, wherein the hole transport layer includes nickel oxide; Applying a first solution on the surface of the hole transport layer to form a hole modification layer, wherein the first solution contains a compound represented by formula (I) and a self-assembled monomolecular material, wherein the self-assembled monomolecular material includes at least one of a compound represented by formula (II) and a compound represented by formula (III); Other functional layers are sequentially prepared on the surface of the hole modification layer, and the other functional layers at least include a perovskite layer, an electron transport layer and a first transparent electrode layer.
12. The preparation method according to claim 11, characterized in that: In the first solution, the mass ratio of the compound represented by formula (I) to the self-assembled monomolecular material is 0.4-2.5:
1.
13. The preparation method according to claim 11, characterized in that: In the first solution, the mass ratio of the compound represented by formula (I) to the self-assembled monomolecular material is 0.6-0.9:
1.
14. The preparation method according to claim 11, characterized in that: The preparation process of the hole modification layer comprises: The first solution is spin-coated on the surface of the hole transport layer, and the hole modification layer is obtained after annealing, wherein the spin-coating speed is 3000rpm~5000rpm, the spin-coating time is 20s~40s, the annealing temperature is 80℃~120℃, and the annealing time is 8min~12min.
15. The preparation method according to any one of claims 11 to 14, characterized in that: The preparation method further comprises: A perovskite layer, an electron transport layer, a buffer layer, a first transparent electrode layer and an anti-reflection layer are prepared on the surface of the hole modification layer.
16. A photovoltaic module, characterized in that: The photovoltaic module comprises the solar cell according to any one of claims 1 to 10, or the photovoltaic module comprises the solar cell prepared by the preparation method according to any one of claims 11 to 15.
Citation Information
Patent Citations
Method for modifying self-assembled hole transport layer by alkali metal acetate
CN114420853A
Lead-tin mixed perovskite solar cell based on self-assembled single layer and preparation method thereof
CN117337115A
